Current Social and Pedagogical Problems Facing the System of Youth Education and Music Education - Mavlyuda Karimova (Researchparks Publishing, 2022)
In the upbringing of young people - the cultural values of the people, the art of music, which is a spiritual heritage, has served for thousands of years as a powerful source of education for the peoples of the East. There are many great artists, writers, directors, painters, teachers who have a worthy place in our recent history and in our spiritual life today. Our community, our young people, want to learn more about their creative work and enjoy their unique art to the fullest. Its effective use and application today is a requirement of the time.